Covariates of elevated blood pressure in young adults : a cross-sectional study in East Coast Malaysia - Wan Omar, Wan Fatein Nabeila; Musa, Ramli; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; A.Talib, Norlelawati; Mohd. Shah, Aida Nur Sharini; Aung, Sithu; Abdullah, Aszrin (2018)
Introduction: Elevated blood pressure, which includes prehypertension and hypertension, have been found to be high among young adults. However, diagnosis in this age group is often delayed and intervention is suboptimal. Methods and materials: A cross- sectional study involving 240 adults was conducted in Kuantan via purposive sampling according to the blood pressure categories. Eighty subjects were each recruited for normotension, prehypertension and newly-diagnosed hypertension groups respectively. Blood pressure parameters, anthropometry and blood were taken for biochemical profile. Bivariable association were analysed using Pearson/Spearman correlation test. Significant variables were then tested via multivariate linear regression. Results: Age, body mass index, waist circumference, creatinine, fasting blood glucose and dyslipidaemia were all found to be positively associated with blood pressure, indicating its significant association with metabolic derangement. In multivariate analyses, age, body mass index and triglycerides were found to be significant covariates of blood pressure elevation. Conclusion: Our data suggests that significant covariates of elevated blood pressure in young adults were age, body mass index and triglycerides.